Pre-run-time schedulability analysis of P-NET fieldbus networks - Tovar, Eduardo (2014)
P-NET is a fieldbus industrial communication standard, which uses a Virtual Token Passing MAC mechanism. In this paper we establish pre-run-time schedulability conditions for supporting real-time traffic with P-NET. Essentially we provide formulae to evaluate the minimum message deadline, ensuring the transmission of real-time messages within a maximum time bound